PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2018 - H. BURHANUDIN; MUHDIN MUHDIN; LUTFIATUN NISA (Universitas Mahasaraswati Mataram, 2020)
This research conducted trough to examine the profitability influence toward company value with corporate social responsibility as moderating variable in sub sector company food and drink which listed at BEI period in 2015-2018, This is associative research with the aim is to find out the influence of or also the relation between two variables or more the sample were received trough sampling purposive technique and were obtained 12 samples with the research period 2015-2018 while data analysis method use panel data regression analysis by eviews 9 program. Research result shows that profitability variable (ROE) have a positive influenced and significant toward value of sub sector company food and drink which listed at BEI period 2015-2018 and variable corporate social responsibility (CSD) is able to moderate the profitability influenced toward value of sector company food and drink which listed at BEI period 2015-2018.The management recommendation to the sub sector company food and drink is should they more consider of the return on equity (ROE) factor and corporate social responsibility (CSD) to increase the company value.